Association of Small Computer Users in Education (ASCUE) Summer Conference Proceedings (29th, North Myrtle Beach, South Carolina, June 9-13, 1996) - Association of Small Computer Users in Education; Smith, Peter; Association of Small Computer Users in Education ([S.l.] : Distributed by ERIC Clearinghouse, 1996)
Papers from a conference on small college computing issues are: "Ethics, Privacy, and Security in Higher Education Technology" (John A. Anderson); "Multimedia in the Classroom: Recollections After Two Years" (Stephen T. Anderson Sr.); "Creating a Computer Competency Requirement for Mary Washington College Students" (David J. Ayersman, Ernest C. Ackermann, and Paul M. Zisman); "Low Cost, Low Tech, Low Brow Technology: A Plan for Campus Communication" (Kurt E. Bernardo); "Back to the Future: Help! It Was 20 Years Ago, and We've Only Just Arrived" (Kate Coffield); "Starting Computer Science Using C++ with Objects: Workable Approach" (Mary V. Connolly); "Web Database Development: Implications for Academic Publishing" (Bob Fernekes); "Using a Computer Program To Enhance an English Course in the Novel" (David Field); "A Team Approach To Managing Technology: Despite Our Differences--We Had To Make IT Work!" (Peter R. Giuliani); "Integrating "Geometer's Sketchpad" into a Geometry Course for Secondary Education Mathematic Majors" (Margaret W. Groman); "1 Thirty Station Math Lab + 2 Faculty = Managing 500 Students Successfully in Low-Level Mathematics Courses" (Tim Hagopian); "The WWW, Preservice Teachers and their Mathematics Courses" (Pat Halpin and Joanne D. Kossegi); "MSCD's Development of a Campus Wide Information System on the World Wide Web" (Mary Hanna); "The Just in Time Approach To Effectively Use Business Software in College Business Courses" (Brian R. Hoyt); "C-CUE: A Regional Consortium in Action" (Frederick Jenny, Daniel Faulk, and William J. Creighton);"Creating an Undergraduate InfoTech Major" (Harold H. Kollmeier); "Process and Facilities as Critical Success Factors in Training and Supporting Faculty To Use Multimedia/Computer Technologies" (Michael E. Kress and Arthur W. Hafner); "Project Vision: An On-Line Learning Initiative for College Freshmen" (Susan V. Monk); "Distance Learning and Today's Educational Environment" (Thomas A. Pollack); "The Computerized 'Assistant Prof'" (J. Stuart Shough); "Developing a CWIS--It's Not a Computing Center Project" (Carol L. Smith and Bonnie M. Nealon); "The Shift to a Learner-Centered University: New Roles for Faculty, Students, and Technology" (Karen L. Smith and J. Timothy Kolosick); "A Process Education Approach To Teaching Computer Science" (Peter D. Smith); "The Paperless Writing Course: A Relevant Business Writing Course" (Michelle Snyder); "Neural Networks for the Beginner" (Robin M. Snyder); "A Personal Multimedia System for Instructional Support" (Robin M. Snyder); "Bridging the Multimedia Generation Gap" (Nancy Thibeault and Janet Hurn); "Using TQM: A New Teaching Model" (Nancy S. Thomson); "Faculty as Partners: A Four-Tiered Training Approach To the Web" (Robin Wagner and Kim Breighner); "Supporting Student PCs on the Campus Network" (Brad Weaver); "The Compressed Video Experience" (John Weber); and "Integrating Courses with the Internet: Preparing the Teacher as well as the Learner" (Arthur E. Williams). (SWC)
ERIC Note: For individual papers, see IR 018 248-279. For 1995 proceedings, see ED 387 088.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Computer Assisted Instruction; Computer Networks; Computer Uses in Education; Educational Technology; Futures (of Society); Higher Education; Information Networks; Internet; Microcomputers; Multimedia Instruction; Teacher Education; Technological Advancement; Telecommunications; Collected Works, Proceedings